A Multidecadal Assessment of Drought Intensification in the Middle East and North Africa: The Role of Global Warming and Rainfall Deficit - Ahmed El Kenawy (7510103) (2025)
This study provides a comprehensive assessment of drought distribution and severity across the Middle East and North Africa (MENA) region from 1981 to 2021, utilizing two widely recognized drought indices: the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI). We employed the CRU TS v. 4.07 datasets to assess changes in drought characteristics (e.g., frequency, intensity, duration, and severity) at the 12-months timescale for the main Koppen-Geiger climate zones in the region. Results indicate a significant shift from wetter conditions before 1998 to more frequent drought occurrences post-1998, particularly in northern MENA, including North Africa, the Levant, and western parts of the Arabian Peninsula, northern Iraq, and western Iran. Both the SPI and SPEI indicate significant positive changes in drought frequency across 19.4% of the MENA region during the period 1998–2021, compared to 12.9% in the earlier period of 1981–1997. The SPEI, which incorporates the effects of evapotranspiration, demonstrated a more pronounced increase in drought frequency and severity than the SPI, reflecting the growing impact of rising temperatures in the most recent decades. The region experienced more frequent and prolonged, but less intense, droughts in the past two decades. Spatially, the SPEI highlighted significant drought intensification in temperate and cold desert (CWb, BWk) zones across the region, primarily driven by increasing air temperatures. On the other hand, SPI tended to capture well the mild and moderate drought events, while it underestimated the severity of the most anomalous dry events (i.e., severe, extreme, and very extreme). For example, in comparison to the SPI, the SPEI indicated an increase of 15% in the areas affected by severe to very extreme droughts in arid regions (Aw). The study also noted discrepancies between the SPI and SPEI in hyper-arid regions like the Sahara and Arabian Peninsula (BWh), emphasizing the importance of using temperature-inclusive indices like SPEI for more accurate drought assessments in warmer and water-limited climates in the region. Our findings indicate that the SPEI can be seen as a more reliable indicator for understanding drought severity in the region in the context of global warming. Overall, our findings emphasize the urgency of adopting adaptation and mitigation strategies to address the increasing frequency and severity of droughts due to global warming. Other Information Published in: Earth Systems and Environment License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41748-025-00576-4